'For this is a trait of a rhetorical and double-tongued man': artifice and ambiguity in Middle Byzantine art. Issue 4 (2nd October 2019) - Frentrop, Lara
ABSTRACT: The State Hermitage Museum in St Petersburg houses a group of small silver and silver-gilt vessels, thought to have been made in Byzantium and dated to the twelfth century. The vessels are decorated with engraved and relief images that predominantly, but not exclusively, refer to the world of secular entertainments: a small vessel from Berezov bears around one hundred tightly stacked, small-scale images that show dancers, musicians, animals, and hybrids, whilst its inside displays a portrait of the warrior saint, St George; a shallow vessel from Vilgort is decorated with images of animals and hunting scenes on its outside, and on its inside bears a central roundel showing a couple surrounded by animals; and a bowl formerly in the collection of the Russian émigré Alexander Basilevsky shows twelve individual figures under arches, including dancers and musicians, on its outside and a pair of griffins on its inside. These three dishes, which will form the focus of this article, and their variegated images confront the viewer (and scholar) with a problem: how should the complex and often ambiguous imagery of the precious metal dishes be interpreted? Is a single, coherent meaning intended by their decoration, or is the latter a jumble of meaningless scenery? The clue to their interpretation can be found, as will be argued, in contemporary rhetorical strategies and performances. Riddles and 'double-tonguedness' prominently featured in twelfth-century rhetorical performances and works, and even, this is suggested, in material culture. Studying visual and rhetorical displays together can illuminate not only the interpretation of individual artworks, but also the broader relationship in medieval Byzantium between rhetoric and the visual arts.